Complete genome sequence of Xanthomonas citri pv. anacardii strain IBSBF2579 from Brazil - Silva Junior, Wilson José (2018)
The bacterium Xanthomonas citri pv. anacardii is the agent of angular leaf spot of the cashew tree (Anacardium occidentale L.). The complete genome sequencing of the strain IBSBF2579 was done on an Illumina HiSeq 2500 platform. The de novo assembly of the X. citri pv. anacardii strain IBSBF2579 genome yielded 133 contigs, with a size of 5,329,247 bp and a G+C content of 64.03%. The prediction was performed by GeneMarkS and the automatic annotation by Rapid Annotations using Subsystems Technology (RAST), with 4,406 identified genes.